ABC's are hauntin' you

Algebra Level 4

If a + b + c = 0 , \Large \color{#D61F06}{a}+\color{#3D99F6}{b}+\color{#20A900}{c} = 0, then a 5 + b 5 + c 5 a b + b c + c a = K a b c . \ \Large \dfrac{\color{#D61F06}{a}^5 + \color{#3D99F6}{b}^5 + \color{#20A900}{c} ^5}{\color{#D61F06}{a}\color{#3D99F6}{b} + \color{#3D99F6}{b}\color{#20A900}{c} +\color{#20A900}{c} \color{#D61F06}{a}}=K\cdot \color{#D61F06}{a}\color{#3D99F6}{b}\color{#20A900}{c}. K = ? \Large K \ = \ ?

Note: Assume that a , b , c a,b,c are not all 0.


The answer is -5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Ricardo Takayama
Nov 24, 2015

Using Newton's Identities for a cubic polynomial:

P 0 = a 0 + b 0 + c 0 = 3 P 1 = a 1 + b 1 + c 1 = 0 P 2 = a 2 + b 2 + c 2 = ( a + b + c ) ( a + b + c ) 2 ( a b + b c + c a ) = 2 ( a b + b c + c a ) P 3 = a 3 + b 3 + c 3 = ( a + b + c ) ( a 2 + b 2 + c 2 ) ( a b + b c + c a ) ( a + b + c ) + 3 a b c = 3 a b c P 4 = a 4 + b 4 + c 4 = ( a + b + c ) ( a 3 + b 3 + c 3 ) ( a b + b c + c a ) ( a 2 + b 2 + c 2 ) + a b c ( a + b + c ) P 5 = a 5 + b 5 + c 5 = ( a + b + c ) ( a 4 + b 4 + c 4 ) ( a b + b c + c a ) ( a 3 + b 3 + c 3 ) + a b c ( a 2 + b 2 + c 2 ) = ( a b + b c + c a ) ( 3 a b c ) + a b c ( 2 ( a b + b c + c a ) ) = 5 a b c ( a b + b c + c a ) \begin{array} { l l l} P_0 & = a ^ 0 + b ^ 0 + c ^ 0 & = 3 \\ P_1 & = a ^ 1 + b ^ 1 + c ^ 1 & = 0 \\ P_2 & = a ^ 2 + b ^ 2 + c ^ 2 & = (a + b + c)(a + b + c) - 2 ( a b + b c + c a)\\ & & = - 2 ( a b + b c + c a) \\ P_3 & = a ^ 3 + b ^ 3 + c ^ 3 & = (a + b + c) (a^2 + b^2 + c^2) - ( a b + b c + c a)(a + b + c) + 3 a b c \\ & & = 3 a b c \\ P_4 & = a ^ 4 + b ^4 + c ^ 4 & = (a + b + c) (a^3 + b^3 + c^3) - ( a b + b c + c a)(a ^2 + b ^2 + c ^2) + a b c ( a + b + c) \\ P_5 & = a ^ 5 + b ^5 + c ^ 5 & = (a + b + c) (a^4 + b^4 + c^4) - ( a b + b c + c a)(a ^3 + b ^3 + c ^3) + a b c ( a ^ 2 + b ^ 2 + c ^ 2) \\ & & = - ( a b + b c + c a) (3 a b c) + a b c (- 2 ( a b + b c + c a)) = - 5 a b c ( a b + b c + c a)\\ \end{array}

Hence, a 5 + b 5 + c 5 a b + b c + c a = 5 a b c ; K = 5 \dfrac{a ^ 5 + b ^5 + c ^ 5}{ a b + b c + c a} = - 5 a b c ; K = -5

Shreyash Rai
Nov 30, 2015

will this be fine?

Yes, it is :)

Ash Ketchup - 4 months, 1 week ago
Lakshya Singh
Dec 1, 2015

A very nice solution

And a cool problem

Shreyash Rai - 5 years, 6 months ago

Hey shreyash can you post some mind boggling questions in algebra?

Lakshya Singh - 5 years, 6 months ago

Log in to reply

I can try but im not much of a maker just a solver

Shreyash Rai - 5 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...